Strategy of Kopi Sembalun Agro-tourism (Study in Sembalun Village, East Lombok Regency, NTB) - Kurniatun, Eni; Hakim, Luchman; Pangestuti, Edriana (The International Journal of Accounting and Business Society, 2023)
Purpose—This research aims to analyze the potential for developing the agrotourism “Kopi Sembalun” in Sembalun Village, East Lombok. Design/methodology/approach — This research used a qualitative approach by observing the Sembalun village areas to see the potential of agritourism activities related to coffee to be developed as a destination of agrotourism. Data were obtained from direct observation and a semi-structured interview with informants. Then, the obtained results were analyzed using the SWOT strategy IFAS and EFAS analysis. Findings — Glamping Sajang, Bukit Pemedengan, Kebun Kopi Amaq Hartono, Kopikey, Sembalun Coffee House, and Rinjani Coffee have more potential than the other places. The direction of the strategy for developing agritourism coffee Sembalun is in quadrant I. An aggressive strategy using the strength opportunity (SO) is the best strategy for agritourism coffee in Sembalun village. The system that will be developed will elevate the history of Sembalun coffee and increase the ability to process coffee as an attraction; expand the marketing of Sembalun coffee by exploiting the potential of nature, maintaining coffee productivity and quality, involving coffee farming communities in the development of coffee agrotourism. Practical implications—This research implication is used by the owner, manager, and community of Sembalun Village to manage and develop Sembalun coffee agrotourism so that Sembalun coffee is increasingly widely known and has an economic impact on coffee farming communities in Sembalun Village. Originality/value —  This paper describes effective solutions for coffee farmers regarding agro-tourism development strategies.